AB0891 Prevalence of Osteoporosis and Vitamin D Deficiency in Patients with Inflammatory Bowel Disease. (9th June 2015) - Rosa-Gonçalves, D.; Bernardes, M.; Vieira, T.S.; Magro, F.; Macedo, G.; Oliveira, A.; Faria, T.; Alves, V.; Perez, M.B.; Pinto, A.S.; Ramos, I.; Pereira, J.G.; et al.
Abstract : Background: The inflammatory bowel disease (IBD) increases the risk for metabolic bone disease due to several factors, including steroid use, increased cytokine production and malabsorption. Objectives: Determine prevalence of osteopenia/osteoporosis (OP) in IBD patients, characterizing their bone metabolism profile.We also intend evaluate correlation between bone mineral density (BMD) and T-score with bone biomarkers (BBM), 25(OH)D3 levels and use of steroids. Methods: Cross-sectional study was conducted in adult IBD patients from a University Hospital in the North of Portugal. Patients who exhibited a controlled IBD were evaluated consecutively by a rheumatologist from June 2013 to December 2014. Age, IBD duration and treatment data were collected. Lumbar spine (LS) and total hip (TH) BMD were analyzed using osteo-densitometer LUNAR Expert 1320. We determined phosphorus, calcium, parathormone (PTH), 25(OH)D3 and BBM (beta- CTx, osteocalcin) levels in the serum. Descriptive statistics was used to report sample's demographic and clinical characteristics. Pearson's correlation was used to evaluate correlation between BMD and T-score with BBM and 25(OH)D3 levels;student t-test was used to evaluate relation with history of use of high-dose steroids. Statistical significance level was set at p<0.05. Results: Total of 57patients were included, with a mean age of 44 years-old (±11.84), the majority females (n=36). Thirty-seven (64.9%) had CD and 20 (35.1%) UC. Mean duration of IBD was 11.95 (±7.71) years. Twenty-six (45.6%) were under biological therapy due to IBD (25 infliximab; 1 adalimumab). Other therapies in use were azathioprine, sulphasalazine and mesalazine. Only 3 patients were under steroids (<10mg/d prednisolone) but 17 patients had a past history of high-dose steroids use. Osteopenia prevalence ranged from 21% (n=12) (TH) to 24.6% (n=14) (LS).The prevalence of OP ranged from 5.3% (n=3) (TH) to 7% (n=4) (LS). Eleven (19.3%) patients had 25 (OH)D3 levels between 20-30ng/mL and 36 (63.2%) had <20ng/mL. Eight (14%) patients had PTH levels >65pg/mL, of which 3 had hipophosphatemia. Seven (12.3%) patients exhibited high bone turn-over (beta- CTx ≥0.28ng/mL and osteocalcin≥31.2ng/mL). Additionally, 25 patients presented with beta- CTx ≥0.28ng/mL. Beta- CTx was correlated with LS and TH T-scores (r=-0.348 and r=-0.303, respectively; p<0.05) and BMD values (r=-0.340 and r=-0.297, respectively; p<0.05). Similarly, osteocalcin was correlated significantly with LS and TH T-scores (r=-0.454 and r=-0.443, respectively; p<0.01) and BMD values (r=-0.472 and r=-0.459, respectively; p<0.01).BMD values and T-score on LS and TH weren't correlated with the disease duration, 25(OH)D3 levels or acute phase reactants.We found that the use of high-doses steroids has a significant effect on BMD and T-score of the TH (p<0.05 for both) but not on the LS (p=0.065 and p=0.093, respectively). Conclusions: High prevalence of osteopenia/osteoporosis and lower serum 25(OH)D3 levels were observed, in both CD and UC patients. The early recognition of problem and more appropriate preventive and treatment strategies are essential. Disclosure of Interest: None declared